An investigation into teacher’s L1 and L2 use in Indonesian EFL classroom - Amriana (Center for Humanities and Innovation Studies, 2018)
Teacher’s L1/L2 use in Indonesian EFL classroom has been the object of debate among practitioners of a second language and foreign language teaching. Despite the considerable amount of research that has been conducted on the phenomenon, the focus has often been on the advantages and disadvantages. This study reports on a study that investigated subject teacher’s language use on Indonesian EFL classroom. It reports research conducted in a private secondary school in Makassar. Ethnography research has been employed to collect data on how the teacher perceives the L1/L2 use and the extent to which the approaches they adopt impact on students’ achievement. The research result demonstrates that the more active the teacher in promoting L2 learning, the more he is aware of the teaching practices used in the classroom. Also, the research result also reveals that the more he improves the quality of his teaching approach, the better language learning his students acquire.